Challenges in a Physics Course: Introducing Student-Centred Activities for Increased Learning - Hernandez, Carola; Ravn, Ole; Forero-Shelton, Manu (Journal of University Teaching and Learning Practice, 2014)
This article identifies and analyses some of the challenges that arose in a development process of changing from a content-based teaching environment to a student-centred environment in an undergraduate physics course for medicine and biology students at Universidad de los Andes. Through the use of the Critical Research model proposed by Skovsmose and Borba, the development process was formed as a close co-operation between academics and researchers in both the construction of pedagogical changes and the responses to particular educational problems during the process. The analyses of the development process highlight a number of difficulties in relation to the introduction of specific student-centred approaches in relation to both the structure of the course and the conception of the content of the course.